Excellent outcomes with adjuvant toremifene or tamoxifen in early stage breast cancer - Jaime D. Lewis; Anees B. Chagpar; Elizabeth A. Shaughnessy; Jacob Nurko; Kelly McMasters; Michael J. Edwards (Опухоли женской репродуктивной системы)
Fareston (toremifene) and tamoxifen, both selective estrogen receptor modulators, are therapeutically equivalent treatments for metastatic breast cancer. We hypothesized that toremifene as compared with tamoxifen given as adjuvant therapy for early stage breast cancer would result in equivalent survival with an improved side effect profile, therefore, providing superior therapeutic efficacy.Subjects and methods. The North American Fareston versus Tamoxifen Adjuvant trial assigned 1813 perimenopausal or postmenopausal women with hormone receptor (HR) – positive invasive breast cancer to adjuvant treatment with either tamoxifen or toremifene. The primary outcomes evaluated were disease-free survival (DFS) and overall survival (OS).Results. Median follow-up was 59 months. The baseline characteristics of the 2 treatment groups were well-balanced. On the basis of intenttotreat, 5-year actuarial DFS was not significantly different between tamoxifen and toremifene (91.2 % (standard error of the mean (SE) 1.2 %) vs 91.2 % (SE 1.1 %), respectively). Similarly, 5-year actuarial OS was not significantly different between tamoxifen and toremifene (92.7 % (SE 1.1 %) vs 93.7 % (SE 1.0 %), respectively). Controlling for patient age, tumor size, and tumor grade, a Cox multivariate survival analysis found no difference between patients randomized to toremifene versus tamoxifen in terms of OS (OR 0.951; 95 % confidence interval (CI), 0.623–1.451, p = 0.951) or DFS (OR 1.037; 95 % CI, 0.721–1.491, p = 0.846). Adverse events were similar in the 2 groups.Conclusions. Women treated with adjuvant hormonal therapy enjoyed excellent DFS and OS. No significant differences were found between treatment with either tamoxifen or toremifene. Treatment of HR-positive patients with either tamoxifen or toremifene is appropriate.